Open Society According Henri Bergson: Its Political Expressions and Anthropological Substantiation - Aleksandravičius, Povilas (Politologija, 2020)
The paper seeks to reveal the Bergson’s conception of open society. In the first part, three concrete political expressions of the open society are identified that are spreading in international relations and inside the society. The second part is aimed at showing that the open society is not a society without borders or limits and it does not pose any dangers to cherishing of identities: Bergson’s concept of duration, the source of his political philosophy, establishes identities by providing the foundation for the dynamic process of their maturation through openness. The anthropological substantiation of the open society that was begun in this part is continued in the third part of the paper that analyses the factors of closing and opening, their roots in nature, human nature and vital impetus.
Keywords: Bergson; open society; social justice; duration; intuition; vital impetus